2021
DOI: 10.1021/acs.jpclett.1c02380
|View full text |Cite
|
Sign up to set email alerts
|

Core Electron Binding Energies in Solids from Periodic All-Electron Δ-Self-Consistent-Field Calculations

Abstract: Theoretical calculations of core electron binding energies are required for the interpretation of experimental X-ray photoelectron spectra, but achieving accurate results for solids has proven difficult. In this work, we demonstrate that accurate absolute core electron binding energies in both metallic and insulating solids can be obtained from periodic all-electron Δ-self-consistent-field (ΔSCF) calculations. In particular, we show that core electron binding energies referenced to the valence band maximum can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 79 publications
3
54
0
Order By: Relevance
“… 17 20 Recently, ΔSCF calculations with meta-GGAs were, in combination with finite-size correction schemes, also successfully applied to simple solids. 21 …”
Section: Introductionmentioning
confidence: 99%
“… 17 20 Recently, ΔSCF calculations with meta-GGAs were, in combination with finite-size correction schemes, also successfully applied to simple solids. 21 …”
Section: Introductionmentioning
confidence: 99%
“…It has been recently shown that the SCAN functional yields excellent absolute and relative CLBEs for molecules 17 and solids. 19 We find that this is also true for the ETFA molecule.…”
Section: Core65 Benchmarkmentioning
confidence: 52%
“…The most popular DFT-based approach is the Delta self-consistent field (∆SCF) method, 13 which has been thoroughly benchmarked. [14][15][16][17][18][19] While high accuracy can be achieved with these approaches, the explicit optimization of a core-ionized wave function leads to conceptual problems, e.g., regarding periodicity, constraining spin-orbit coupled states or, in the case of DFT, deteriorating accuracy for larger structures, which was already discussed and demonstrated elsewhere. [20][21][22][23][24] An explicit orbital optimization of core-ionized systems and the related conceptual issues are avoided in response theories, where electron propagators are applied to transform the ground into an excited state.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond ∆SCF approaches, the XPS spectra of periodic systems have also been computed by GW methods [90,91]. We find of particular interest the work Zhu et al [90] where an implementation based on crystalline Gaussian Basis set for the computation of core-electrons BEs on periodic systems in the GW scheme, is presented.…”
Section: Computational Tools For the Computation Of Xps Spectra: Firs...mentioning
confidence: 99%